2019
DOI: 10.1002/cne.24682
|View full text |Cite
|
Sign up to set email alerts
|

Altered cochlear innervation in developing and mature naked and Damaraland mole rats

Abstract: Compared to many other rodent species, naked mole rats (Heterocephalus glaber) have elevated auditory thresholds, poor frequency selectivity, and limited ability to localize sound. Because the cochlea is responsible for encoding and relaying auditory signals to the brain, we used immunofluorescence and quantitative image analysis to examine cochlear innervation in mature and developing naked mole rats compared to mice (Mus musculus), gerbils (Meriones unguiculatus), and Damaraland mole rats (Fukomys damarensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
(110 reference statements)
1
11
0
Order By: Relevance
“…(See details provided in the materials and equipment section below). Note: This protocol has been used to isolate the sensory epithelium of various rodents (e.g., Barone et al. 2019 ), including aged rodents.…”
Section: Before You Beginmentioning
confidence: 99%
See 3 more Smart Citations
“…(See details provided in the materials and equipment section below). Note: This protocol has been used to isolate the sensory epithelium of various rodents (e.g., Barone et al. 2019 ), including aged rodents.…”
Section: Before You Beginmentioning
confidence: 99%
“…No changes in the protocol described here are necessary when using a different strain/line. Moreover, this protocol has been successfully applied to other rodents, including rats (e.g., McLean et al., 2009 ) as well as gerbils and various mole rats ( Barone et al., 2019 , Pyott et al., 2020 ). d Various probes can be used depending on the experimental design.…”
Section: Key Resources Tablementioning
confidence: 99%
See 2 more Smart Citations
“…A study using microcomputed tomography concluded that the gross dimensions of the middle and inner ear, including cochlear length, are not sufficient to explain altered hearing in bathyergids [14]. Another study reported alterations in the patterns of innervation of the cochlear hair cells in naked and Damaraland mole-rats (Fukomys damarensis) compared with mice and gerbils, but these alterations are again not sufficient to explain the decreased hearing sensitivity in mole-rats [15]. Finally, the most comprehensive examination of auditory function has been performed in Fukomys anselli.…”
Section: Introductionmentioning
confidence: 99%